Angiotensin (1-7) peptide replacement therapy with plasma transfusion in COVID-19 - Onal, Hasan; Ergun, Nurcan Ucuncu; Arslan, Bengu; Topuz, Seyma; Semerci, Seda Yilmaz; Ugurel, Osman Mutluhan; Topuzogullari, Murat; Kalkan, Ali; Yoldemir, Sengul Aydin; Suner, Nurettin; Kocatas, Ali (PERGAMON-ELSEVIER SCIENCE LTD, 2022)
Aim: To determine whether convalescent angiotensin (1-7) peptide replacement therapy with plasma (peptide plasma) transfusion can be beneficial in the treatment of critically ill patients with severe coronavirus 2 (SARS-CoV-2) infection.Study design: Case series of 9 critically ill patients with laboratory-confirmed COVID-19 who met the following criteria: severe pneumonia with rapid progression and continuously high viral load despite antiviral treatment. Peptide plasma: Plasma with angiotensin (1-7) content 8-10 times higher than healthy plasma donors was obtained from suitable donors. Peptide plasma transfusion was applied to 9 patients whose clinical status and/or laboratory profile deteriorated and who needed intensive care for 2 days.Results: In our COVID-19 cases, favipiravir, low molecular weight heparin treatment, which is included in the treatment protocol of the ministry of health, was started. Nine patients with oxygen saturation of 93% and below despite nasal oxygen support, whose clinical and/or laboratory deteriorated, were identified. The youngest of the cases was 36 years old, and the oldest patient was 85 years old. 6 of the 9 cases had male gender. 3 cases had been smoking for more than 10 years. 4 cases had at least one chronic disease. In all of our cases, SARS CoV2 lung involvement was bilateral and peptide plasma therapy was administered in cases when oxygen saturation was 93% and below despite nasal oxygen support of 5 liters/minute and above, and intensive care was required. Although it was not reflected in the laboratory parameters in the early period, 8 patients whose saturations improved with treatment were discharged without the need for intensive care. However, a similar response was not obtained in one case. Oxygen requirement increased gradually and, he died in intensive care process. An increase of the platelet count was observed in all cases following the peptide plasma treatment.Conclusion: In this preliminary case series of 9 critically ill patients with COVID-19, administration of plasma containing angiotensin (1-7) was followed by improvement in their clinical status. The limited sample size and study design preclude a definitive statement about the potential effectiveness of this treatment, and these ob-servations require evaluation in clinical trials.
Keywords: Turkey; COVID-19; ACE2; Angiotensin (1-7); SARS-CoV-2; Plasma; CONVERTING ENZYME 2; RECEPTOR MAS; SARS CORONAVIRUS; GENETIC DELETION; METABOLISM; ANG-(1-7); PROTEIN; Hematology